2018
DOI: 10.1136/bmjgast-2018-000207
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of sofosbuvir plus ribavirin for chronic hepatitis C genotype 2 in Asia: a systematic review and meta-analysis

Abstract: BackgroundSofosbuvir plus ribavirin (SOF+RBV) for 12 weeks is the standard treatment for chronic hepatitis C (CHC) genotype 2 (GT2) in most of Asia despite availability of new CHC medications. SOF-RBV real-world effectiveness has only been reported in small and/or single-centre studies. Our goal was to determine the real-world effectiveness of 12-week SOF+RBV therapy for CHC GT2 in Asia.MethodsA systematic search on PubMed and Embase was conducted through 30 June 2017. We identified full articles and conferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…Among cirrhotic patients who received SOF/RBV, the SVR 12 rates for treatment‐experienced and treatment‐naïve patients were 83.3% and 92.3%, respectively. The 9% gap of SVR 12 rate between these patients was in line with a recent meta‐analysis for Asian HCV‐2 patients receiving SOF/RBV where the SVR 12 rates were 84.5% and 93.3% for treatment‐experience and treatment‐naïve cirrhotic patients, respectively . However, the gap of SVR 12 rate in Western treatment‐experienced and treatment‐naïve HCV‐2 cirrhotic patients who received SOF/RBV for 12 weeks in FISSION, FUSION, and POSITRON trials was about 30% .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Among cirrhotic patients who received SOF/RBV, the SVR 12 rates for treatment‐experienced and treatment‐naïve patients were 83.3% and 92.3%, respectively. The 9% gap of SVR 12 rate between these patients was in line with a recent meta‐analysis for Asian HCV‐2 patients receiving SOF/RBV where the SVR 12 rates were 84.5% and 93.3% for treatment‐experience and treatment‐naïve cirrhotic patients, respectively . However, the gap of SVR 12 rate in Western treatment‐experienced and treatment‐naïve HCV‐2 cirrhotic patients who received SOF/RBV for 12 weeks in FISSION, FUSION, and POSITRON trials was about 30% .…”
Section: Discussionsupporting
confidence: 83%
“…The 9% gap of SVR 12 rate between these patients was in line with a recent meta-analysis for Asian HCV-2 patients receiving SOF/RBV where the SVR 12 rates were 84.5% and 93.3% for treatment-experience and treatment-naïve cirrhotic patients, respectively. 35 However, the gap of SVR 12 rate in Western treatment-experienced and treatment-naïve HCV-2 cirrhotic patients who received SOF/RBV for 12 weeks in FISSION, FU-SION, and POSITRON trials was about 30%. 11,12 Whether extending the treatment duration of SOF/RBV to 16 weeks in East-Asian treatment-experienced HCV-2 cirrhotic patients to improve the SVR 12 rate needs further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, very encouraging is that our real‐world results are similar to what was obtained in the clinical trials for GT6, as have also been found for other genotypes for Asians . The SVR results for LDV+SOF in our study were similar to a study conducted by Gane et al who studied 126 HCV patients in which 25 were GT6 and were either treatment naïve or treatment experienced and were treated with LDV+SOF for 12 weeks.…”
Section: Discussionsupporting
confidence: 89%
“…cirrhotic patients with prior treatment failure) are required to receive treatment for a longer duration. 8,9 The fixed-dose combination of ledipasvir (LDV), a non-structural protein 5A (NS5A) inhibitor, and SOF, an NS5B polymerase inhibitor, is given in a single tablet (90 mg LDV and 400 mg SOF) taken orally once daily. Since 2014, LDV/SOF has been approved in many countries across the world for the treatment of HCV genotypes 1, 4, 5, and 6.…”
Section: Introductionmentioning
confidence: 99%